2022
DOI: 10.3389/fpsyg.2022.922503
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chatbot Service Recovery With Emotion Words on Customer Satisfaction, Repurchase Intention, and Positive Word-Of-Mouth

Abstract: This study sought to examine the effect of the quality of chatbot services on customer satisfaction, repurchase intention, and positive word-of-mouth by comparing two groups, namely chatbots with and without emotion words. An online survey was conducted for 2 weeks in May 2021. A total of 380 responses were collected and analyzed using structural equation modeling to test the hypothesis. The theoretical basis of the study was the SERVQUAL theory, which is widely used in measuring and managing service quality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 97 publications
1
4
0
2
Order By: Relevance
“…This supports the human tendency to be positive and socially motivated. Beyond fundamental research, the ratings are also of value in applied settings, such as in communication in healthcare (Stortenbeker et al, 2018) or in the use of chatbots (Yun & Park, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This supports the human tendency to be positive and socially motivated. Beyond fundamental research, the ratings are also of value in applied settings, such as in communication in healthcare (Stortenbeker et al, 2018) or in the use of chatbots (Yun & Park, 2022).…”
Section: Discussionmentioning
confidence: 99%
“… Singh and Pandey (2024) also indicated that inefficient collaboration with AI devices is also a critical barrier to their usage. Yun and Park (2022) , conversely, found that the reliability of chatbot service quality positively impacts users’ satisfaction and repurchase intention. Regarding psychological barriers, Chen et al (2022) found that individuals’ perceived tradition barriers to changes in established ticketing habits brought about by mobile ticketing services were key predictors of resistance, and that those with a negative perception of online banking were more likely to display subsequent resistance ( Kuisma et al, 2007 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 94%
“…In his research on Tunisian Islamic banks, Abdelhadi (2021) [1] discovered that responsiveness has a favorable impact on client satisfaction. However, no substantial correlation between responsiveness and customer satisfaction was discovered by Yun and Park (2022) [69] , Famiyeh et al, (2018) [18] , or Fida et al, (2020) [20] . According to Sardana and Bajpai (2020) [59] , responsiveness was essential for e-banking to satisfy customer expectations (satisfaction).…”
Section: Responsivenessmentioning
confidence: 95%